Faktor-Faktor yang berhubungan dengan penyapihan oleh ibu yang mempunyai balita usia 2 tahun di Calang Aceh Jaya - Mia Audina; Yulia Fitri (Jurnal SAGO Gizi dan Kesehatan, 2019)
Background: Weaning is a process of cessation of breastfeeding by breastfeeding not as expected. Weaning is also a process of stopping breastfeeding in infants. Indonesia Demographic Health Data (IDHS) there are 52% of mothers who give exclusive breastfeeding to infants, and the average duration of breastfeeding is 19 months.Objective: The study aims to measure the factors associated with weaning by mothers with children aged 2 years in Calang, Aceh Jaya.Method: This type of research is analytic descriptive with a cross sectional approach. Research has been carried out in Calang, Aceh Jaya. The number of samples taken in the study amounted to 34 mothers who have toddlers aged 2 years. The study was conducted in 2016. Primary data include sample identity in the form of name, age, date of birth, occupation, level of education, and children collected by direct interview using a questionnaire. This analysis uses the SPSS program, including the chi-square statistical test.Results: The results of this study indicate that there is a relationship between maternal employment for weaning (p = 0.032), there is a relationship between maternal knowledge of weaning (p = 0.043), there is a relationship between maternal health for weaning (p = 0.038), there is a relationship between maternal pregnancy distance against weaning with a value (p = 0.032).Conclusion: Factors related to weaning are maternal occupation, knowledge, maternal health, and maternal pregnancy distance. Need to increase education and health promotion for breastfeeding mothers related to the importance of weaning at the age of 24 months.